She Let Herself Go : Poems - Lyon, George Ella, 1949- (Book collections on Project MUSE., 2012)
From George Ella Lyon comes a dynamic and humorous collection examining the transformations of one woman's life as she tries on, takes on, and peels off identities learned from family stories, gender, fairy tales, and myths. She Let Herself Go spirals through girlhood, wifehood, motherhood, and writerhood, through the poet's evolution, casting a discerning-and often irreverent-eye on the cultural expectations that have shaped her. Claiming Virginia Wolf as word-mother, these poems converse with powerful feminist poets, including Muriel Rukeyser, Ruth Stone, and Grace Paley.